THE USE OF WHAT COMES NEXT TECHNIQUE (WCNT) TO TEACH ACTION VERBS - Wiranto, Irfan Agung; Sutapa, Yohanes Gatot; Bunau, Eusabinus (FKIP - Universitas Tanjungpura, 2020)
The purpose of this research is to know whether What Comes Next technique affected significantly on learners action verbs achievement and to know the effect size of the technique. The form of this research is pre-experimental study with one group pretest and posttest design. The population was all the eleventh grade learners of SMA Negeri 3 Pontianak. By using cluster random sampling technique, the sample was XI Science 6 class consisted of 33 learners. The data collection technique was measurement technique and the tool of data collection was a test consisted of 25 items in the form of multiple choice. The result of the T-test was 12.25. It was higher than t-critical score (12.25 > 2.03). This indicated that the null hypothesis (H0) was rejected and the alternative hypothesis (Ha) was accepted, meaning that What Comes Next Technique affect significantly in teaching vocabulary for the eleventh grade learners in SMA Negeri 3 Pontianak in the academic year of 2019/2020. The score of the effect size of the treatment was 2.08 and classed as Strong effect. As a result, it can be concluded that What Comes Next Technique give a strong effect in teaching vocabulary for the eleventh grade learners in SMA Negeri 3 Pontianak in the academic year of 2019/2020.